Contextualisation of business processes. (9th July 2008) - Rosemann, Michael; Recker, Jan; Flender, Christian
Flexibility has emerged as an important requirement in the design of business processes. Research on process flexibility, however, has traditionally been focused on the intrinsic capability of a process to adapt to a new environment (e.g. workflow escalation, ad hoc modelling). This paper proposes to extend the existing body of research by studying the extrinsic drivers for process flexibility, that is, the root causes that actually drive the demand for flexible business processes. The drivers for flexibility can be found in the context of a process and may include among others time, location, weather, legislation or performance requirements. We argue for a stronger and more explicit consideration of these contextual factors in the design of business processes in order to make processes more adaptive. This paper discusses why context matters and how context can be conceptualised, classified and integrated with existing approaches to business process modelling. We use a goal-oriented process modelling approach to be able to identify relevant context elements and propose a framework and a meta model for classifying relevant context. These extensions are an essential foundation for the definition and implementation of truly agile processes, and as such of high practical and theoretical value.